2001
DOI: 10.1038/sj.gt.3301550
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo reporter system for measuring increased inclusion of exon 7 in SMN2 mRNA: potential therapy of SMA

Abstract: Spinal muscular atrophy (SMA) is a degenerative motor neu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 26 publications
1
89
0
Order By: Relevance
“…Previously, compounds have been identified which alter the incorporation of exon 7 in the SMN transcript from the SMN2 gene (32,33,35). In the present study, compounds such as forskolin and dibutyryl cAMP were shown to increase the expression of the SMN2 gene.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previously, compounds have been identified which alter the incorporation of exon 7 in the SMN transcript from the SMN2 gene (32,33,35). In the present study, compounds such as forskolin and dibutyryl cAMP were shown to increase the expression of the SMN2 gene.…”
Section: Discussionmentioning
confidence: 53%
“…The presence of SMN2 in all SMA patients, the ability of more copies of SMN2 to modify the SMA phenotype, and the rescue of SMA mice by multiple copies of SMN2 make it an attractive therapeutic candidate. Molecules capable of inducing SMN2 expression (30,31) or altering the splicing of SMN2 such that more full-length SMN transcript is produced have been identified (32)(33)(34)(35)(36)(37). At the present time, there is limited information on the mode of action of these compounds as well as the protein complexes that interact with the SMN promoter.…”
mentioning
confidence: 99%
“…Both butyrate and valproic acid are known to act as histone deacetylase inhibitors enhancing transcription of some genes, among which are splicing factors of the SR family, whereas aclarubicin seems to increase the expression of transcription factors (38). Last, sodium vanadate has been reported to inhibit ATPase, alkaline, and tyrosine, as well as multiple other phosphatases, and its likely targets are SR proteins, snRNPs, and hnPNPs (39). This remark about the lack of specificity also stands for drugs that interfere with the kinase activity of DNA topo I.…”
Section: Discussionmentioning
confidence: 99%
“…14 As an indirect measurement of U7 snRNA expression, we analysed exon 7 inclusion in HeLa cells stably expressing an SMN2-luciferase reporter gene. 23 When these HS2 cells were transduced with pLV-T carrying the U7-ESE-B cassette, they showed a strong GFP fluorescence correlating with the expected increase in exon 7 inclusion of the SMN2 reporter gene, from a basal 13 ± 3 to 75 ± 7% (Figures 1d and e). These cells were subsequently transduced with a second lentiviral vector encoding the tTR-KRAB regulatory protein and a dsRed reporter gene and cultured either in the absence or in the presence of doxycycline.…”
Section: Development Of a Regulatable U7 Expression Systemmentioning
confidence: 78%
“…14,23 HeLa-705 cells stably express the human b-globin gene carrying the IVS2-705 mutation. 24 Conditions for cell culture, DNA transfections, lentiviral vector production in 293-T cells, titration on HeLa cells and transduction have been described.…”
Section: Cell Culturementioning
confidence: 99%